Successful treatment with olanzapine and aripiprazole of a schizophrenic patient who developed priapism after switching from risperidone to paliperidone - Saki Kawahara; Kazuyuki Watanabe; Kazuhiko Inazumi; Makoto Kimura; Yuki Hirose; Hiraki Koishikawa (Neuropsychopharmacology Reports)
Abstract Background Ischemic priapism is a rare pathological condition, and delayed intervention can result in irreversible sequelae. Most cases are attributed to the use of antipsychotics. The blockade of α1‐adrenergic receptors is thought to be associated with the disease onset, although data supporting this hypothesis are lacking. No consensus regarding the optimal choice of medication is available. Case Presentation A 59‐year‐old man with schizophrenia, who had been receiving long‐acting injections of risperidone, developed ischemic priapism after receiving paliperidone treatment. Following improvement in ischemic priapism, we administered a combination of aripiprazole and olanzapine, which improved his psychiatric symptoms. We did not observe any recurrence of ischemic priapism. Conclusions Switching the antipsychotic drug causing ischemic priapism to patients having a relatively low affinity for α1‐adrenergic receptors may enable the treatment of schizophrenia without recurrence of ischemic priapism. In addition to the affinity for α1‐adrenergic receptor, differences in metabolic enzyme types and antipsychotic doses may be involved in the occurrence of ischemic priapism. Accumulating evidence is necessary to establish guidelines for selecting medication of patients with ischemic priapism.